MicroRNA‐125b‐5p Regulates Hepatocyte Proliferation During the Termination Phase of Liver Regeneration. Issue 12 (15th September 2020) - Yang, Dakai; Dai, Zhen; Yang, Taihua; Balakrishnan, Asha; Yuan, Qinggong; Vondran, Florian W.R.; Manns, Michael P.; Ott, Michael; Cantz, Tobias; Sharma, Amar Deep
Abstract : The ability of the liver to regenerate and restore mass limits the increasing mortality rate due to life‐threatening liver diseases. Successful liver regeneration is accomplished in multiple stages, of which the priming and proliferation phases are well studied. However, the regulatory pathways, specifically microRNA (miRNA)‐mediated posttranscriptional regulation, which prevent uncontrolled proliferation and mediate the termination of liver regeneration, are not well understood. We identified differentially regulated miRNAs during the termination phase after 2/3 partial hepatectomy (PH) in mice, which is a well‐established mouse model of liver regeneration. We further evaluated the function of differentially regulated miRNAs in primary mouse hepatocytes by using mimics and inhibitors and in vivo by using adeno‐associated virus (AAV) serotype 8. A candidate miRNA target was identified by messenger RNA array in silico analyses and validated in primary mouse and human hepatocytes. Using miRNA profiling, we discovered miR‐125b‐5p as a novel regulator of hepatocyte proliferation in the late phase of liver regeneration. AAV‐mediated miR‐125b‐5p delivery in mice enhanced the endogenous regenerative capacity and resulted in improved restoration of liver mass after 2/3 PH. Further, we found that ankyrin repeat and BTB/POZ domain containing protein 1 ( Abtb1) is a direct target of miR‐125b‐5p in primary mouse and human hepatocytes and contributes to the pro‐proliferative activity of miR‐125b‐5p by forkhead box G1 (FOXG1) and the cyclin‐dependent kinase inhibitor 1A (p21) pathway. Conclusion: miR‐125b‐5p has an important role in regulating hepatocyte proliferation in the termination phase of liver regeneration and may serve as a potential therapeutic target in various liver diseases that often exhibit deregulated hepatocyte proliferation.